Lead market factors for global innovation: Emerging evidence from India - Rajnish Tiwari; Cornelius Herstatt (Hamburg University of Technology (TUHH), Institute for Technology and Innovation Management (TIM), 2011)
Securing access to lead markets is generally regarded as a key driver for the increasing globalization of innovation since these are considered to be early indicators for emerging customer needs. Such markets, therefore, offer a good chance of uncertainty reduction for in the innovation process of firms. Lead markets are generally defined in terms of product segments within national boundaries and are thought to exist in economies with high per capita income, highly sophisticated markets and high international visibility. We argue that there is increasing evidence of lead market tendencies in certain emerging economies, e.g. India. Both domestic and foreign-owned firms there, in recent years, have produced several internationally acclaimed frugal innovations such as the Tata Nano or GE's handheld ECG machine Mac400. Using several examples we demonstrate that India seems to have emerged as a global hub for low-cost, frugal innovations. In this paper, we seek to crystallize the role of lead markets in globalization of R&D and identify the need for an update/extension to better reflect the changed ground realities. On the basis of emerging evidence we propose that sustained economic growth, voluminous markets, strong domestic technological capabilities, presence of foreign-owned R&D, and favorable government policies may be able to offset some of the disadvantages rooted in traditional deficiencies. Engaging a developing country lead market may be useful for firms in securing better access to markets at the bottom of the economic pyramid worldwide.
Keywords: 650; globalization of innovation; lead markets; internationalization of R&D; frugal innovations; bottom of the pyramid